Impact of Treating Asymptomatic Bacteriuria in Kidney Transplant Recipients: A Prospective Cohort Study - Sara Fontserè; Carmen Infante-Domínguez; Alejandro Suárez-Benjumea; Marta Suñer-Poblet; Carmen González-Corvillo; Guillermo Martín-Gutiérrez; Gabriel Bernal; Jerónimo Pachón; María Eugenia Pachón-Ibáñez; Elisa Cordero (MDPI AG, 2021)
This study aims to define the epidemiologic, clinical, and microbiological features of asymptomatic bacteriuria (AB) and cystitis in kidney transplantation recipients (KTRs), and to determine the impact of antimicrobial therapy of AB and the risk factors of cystitis. We conducted a prospective observational study of AB and cystitis in KTRs from January to June 2017. One-hundred ninety seven KTRs were included: 175 (88.8%) with AB and 22 (11.2%) with cystitis. The most frequent etiologies were Escherichia coli, Klebsiellapneumoniae, Enterococcusfaecalis, and Pseudomonas aeruginosa. No differences were observed regarding the etiologies, antimicrobial susceptibility patterns, and microbiologic outcomes in AB vs. cystitis. The treatment of AB diminished the microbiological cure and increased the rates of microbiologic relapses and reinfections; in addition, treated AB patients showed a trend of developing symptomatic urinary tract infection in the following six months. The analysis of the data identified the following independent risk factors for cystitis during the six months of follow-up: AB treatment, thymoglobulin induction, previous acute pyelonephritis, and time since transplantation < 1 year. In summary, considering the lack of clinical benefits of treating AB and its impact on cystitis development in the follow-up, we support the recommendation of not screening for or treating AB.